In vitro biocompatibility of hydroxyapatite‐added GIC: An SEM study using human periodontal ligament fibroblasts. Issue 6 (13th July 2017) - Thomas, Betsy; Gupta, Kunal
ABSTRACT: Objective: Nano‐hydroxyapatite‐added GIC has been developed to improve the physical properties of conventional GIC. However, biological response of periodontal cells to this potentially useful cervical restorative material has been unexplored. The aim of this study was to investigate the in vitro response of human periodontal ligament fibroblasts to hydroxyapatite‐added GIC. Materials and Methods: Three categories of materials, namely, test group 1 (cGIC or type IX GIC), test group 2 (HA‐GIC or hydroxyapatite‐added GIC), and positive control (glass cover slips) were incubated with human periodontal ligament fibroblasts. The samples were viewed under scanning electron microscope to study the morphological characteristics of fibroblasts. Additionally, elemental analysis was performed to differentiate between the two test groups based on surface chemical composition. Results: Test group 1 (cGIC) exhibited cells with curled up morphology, indicative of poor attachment to the substrate. Test group 2 (Ha‐GIC) exhibited cells with flattened morphology and numerous cellular extensions such as lamellipodia and blebs, indicative of good attachment to the substrate. The test group 2 (Ha‐GIC) demonstrated higher surface elemental percentages of calcium and phosphorus. Conclusion: Within the limitations of this study, it may be concluded that hydroxyapatite‐added GIC is more biocompatible than conventional GIC (type IX), probably attributed to high elemental percentages of calcium and phosphorus. Clinical significance: The search for an ideal cervical restorative dental material has been ever elusive. Hydroxyapatite‐added GIC is a simple and economical dental material to fabricate from basic conventional GIC. The results from this study strengthen its candidature for cervical and root surface restorations which may later require soft tissue augmentation. The possibility of connective tissue adhesion to this material is an exciting prospect in the field of periorestorative dentistry.